Tingkat Infeksi Cacing Hati Kaitannya dengan Kerugian Ekonomi Sapi Potong yang Disembelih di Rumah Potong Hewan Wilayah Eks-Kresidenan Banyumas - Munadi Munadi (Jurnal Agripet, 2011)
The level of liver flukes infection and its relation to the economic loss of beef cattle at the abattoir of banyumas ex-residentABSTRACT. The aims of this study was (i) to find out the level of liver flukes infection based on body weight, age of beef cattle and their background of origin, and (ii) to know the relationship between the level of liver flukes infection, body weight, age, background of origin and the level of economic losses of beef cattle. This study was conducted at four abattoir located at Banyumas, Cilacap, Purbalingga and Banjarnegara regencies, Central Java province. The sample was taken by purposive sampling. 20 beef cattle that infected by liver fluke in each abattoir were involved in this study. Multiple linear regression was applied in data analysis. This study revealed that (1) Average of the liver flukes infection level in this areas was 47 present. (2) Under 1-2 of age, the highest liver flukes infection level found at thin body condition (53%) and moderate (31%); under 2,5-3 of age, they are found at fat body condition (75%) and moderate (62%); under 3,5-4 of age the highest liver flukes infection level found at moderate and far body condition (100% and 67%, respectively). (3) Economic loss of beef cattle (Y) affected by factors of the liver flukes infection level (X1), body weight (X2), age (X3), background of origin (Dummy) with determinant coefficient 0,625 and regression equation as fallow; Y = 18792,397 + 207,334 X1 - 17,905 X2 1981,969 X3 - 1178,544 D.